(untitled) (Cadernos do Laboratorio Xeolóxico de Laxe. Revista de Xeoloxía Galega e do Hercínico Peninsular, 2022)
The field work, backscattered electron images and detailed microanalyses of three generations of tourmaline from the Namacotche LCT pegmatites allows de distinction between the compositional magmatic and hydrothermal tourmalines. The generation 1 occurs in the outer intermediate zone of the pegmatite. It consists of zoned crystals with an oscillatory inner core of foitite and schorl, an outer core of schorl and an Fe-rich fluor-elbaite rim. Unzoned Fe-rich fluor-elbaite crystals occur in the inner intermediate zone of the pegmatite. All the crystals are derived by fractionation of a (Al, Li, B)-rich pegmatite melt. However, the rim of zoned crystals and some compositions of unzoned crystals show evidence of hydrothermal fluids, as they plot outside the fractionation trends. The zoned fluor-elbaite crystals of the generation 2 are from the inner intermediate zone of the pegmatite. They have a pink core and a green rim. The rim has higher YFe2+, Na, F contents YFe2+/(YFe2++Licalc.) value and lower Si, YAl, Licalc. and X-site vacancy contents, X-vacancy/(Na+X-vacancy) value than the core. Both zones are hydrothermal. The rim is an overgrowth. The fluor-elbaite gemmy crystals of the generation 3 occur in sheared breccia blasts and clasts with a cookeite matrix. They depend mainly on the fluid-rich hydrothermal environment of low temperatures (280-150ºC). Some from the cycle a may result from the dissolution of magmatic tourmaline crystals of the generation 1 from the sheared outer and inner intermediate zones of the pegmatite due to reaction with late fluids in chemical disequilibrium, followed by growth of tourmaline with low temperature hydrothermal fluids. The evolution from the cycle a to the cycle b and to the cycle c of the generation 3 implies that the hydrothermal reacting fluids were undergoing fractionation and becoming richer in Li and poorer in Fe2+ during the late hydrothermal crystallization of the pegmatites.